Developing a Silk Fibroin Composite Film to Scavenge and Probe H2O2 Associated with UV-Excitable Blue Fluorescence - Chung, Tze-Wen; Chang, Chun-Yi; Chang, Chun-Ning; Liao, Chiu-Hsun; Jan, Yun-Jen; Chen, Li-Ting; Chen, Weng-Pin (Sensors (Basel, Switzerland), 2020)
A silk fibroin composite film that can simultaneously scavenge and probe H2O2 in situ was developed for possibly examining local concentrations of H2O2 for biomedical applications. A multi-functional composite film (GDES) that consists of graphene oxide (G), a photothermally responsive element that was blended with polydopamine (PDA, D)/horseradish peroxidase (HRP, E) (or DE complex), and then GDE microaggregates were coated with silk fibroin (SF, S), a tyrosine-containing protein. At 37 °C, the H2O2-scavenging ability of a GDES film in solution at approximately 7.5 × 10−3 μmol H2O2/mg film was the highest compared with those of S and GS films. The intensities of UV-excitable blue fluorescence of a GDES film linearly increased with increasing H2O2 concentrations from 4.0 μM to 80 μM at 37 °C. Interestingly, after a GDES film scavenged H2O2, the UV-excitable blue fluorescent film could be qualitatively monitored by eye, making the film an eye-probe H2O2 sensor. A GDES film enabled to heat H2O2-containing samples to 37 °C or higher by the absorption of near-IR irradiation at 808 nm. The good biocompatibility of a GDES film was examined according to the requirements of ISO-10993-5. Accordingly, a GDES film was developed herein to scavenge and eye-probe H2O2 in situ and so it has potential for biomedical applications.